Internal Chelation within Functionalized Organoindium Reagents: Prospects for Regio- and Stereocontrol in the Allylation, Propargylation and Allenylation of Carbonyl Compounds - Zambroń, Bartosz K. (Synthesis, 2020)
The low basicity, selective nucleophilicity, and mildness of organoindium compounds allow for the incorporation of many important yet sensitive functional groups into their structure, including examples capable of intramolecularly chelating the indium center within these reagents. The specific nature of such chelated organoindiums causes the reactions involving them to proceed in a unique manner, often with regio- and stereoselectivity inaccessible with simple organometallic reagents. This review covers the rare examples of regio- and stereoselective allylation, propargylation, and allenylation of carbonyl compounds with chelated organoindiums, including brief descriptions of the applications of the resulting adducts in the asymmetric synthesis of natural products and synthetic targets of biological and medicinal interest.1 Introduction2 Internal Chelation Control in the Allylation Processes2.1 Allylindiums with a Chelating Center at the γ-Position2.2 Allylindiums with a chelating Center at the δ-Position2.3 Allylindiums with a Chelating Center at ε- and ζ-Positions2.4 Allylindiums with a Chelating Center at γ′- and δ′-Positions3 Internal Chelation Control in Propargylation and Allenylation Processes3.1 Additions of Chelated Allenylindiums3.2 Additions of Chelated Propargylindiums4 Conclusion
Keywords: organoindiums; internal chelation; stereoselective allylation; propargylation; allenylation